2021
DOI: 10.3390/pr9010128
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive Wear Behavior of CNT-Filled Unidirectional Kenaf–Epoxy Composites

Abstract: Kenaf (Hibiscus Cannabinus) fibers have received significant attention for replacing the usage of synthetic fibers, especially glass fiber, in the fabrication of fiber-reinforced polymer (FRP) composites. The aim of this research was to study the change in wear behavior of kenaf-epoxy fiber composites by filling them with multiwall carbon nanotubes (MWCNT). In particular, the effect of untreated MWCNT (PMWCNT), acid-treated MWCNT (AMWCNT), and silane-treated MWCNT (SMWCNT) was studied, using three different MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This combination and stacking sequence of fiber orientation have never been used before for comparing mechanical and wear characteristics. Currently, there is limited work on the phenomena of abrasive wear in multi-pass settings [19,[33][34][35][36]. The present findings could lead to a rise in the use of GNP/Carbon fiber reinforced epoxy composites.…”
Section: Introductionmentioning
confidence: 73%
“…This combination and stacking sequence of fiber orientation have never been used before for comparing mechanical and wear characteristics. Currently, there is limited work on the phenomena of abrasive wear in multi-pass settings [19,[33][34][35][36]. The present findings could lead to a rise in the use of GNP/Carbon fiber reinforced epoxy composites.…”
Section: Introductionmentioning
confidence: 73%
“…Many countries have already started utilizing natural ller-based composites in various applications, such as rail and decking products, car components, architectural moldings, and more. [52][53][54] Inorganic llers include various materials like zinc oxide, alumina, calcium carbonate, and silica, while organic llers consist of particulates derived from plants and animals. The quantity of ller added to the polymer matrix depends on the type of ller and matrix used, usually varying between 4% and 5% by weight.…”
Section: Introductionmentioning
confidence: 99%
“…As far as wear resistance is concerned, early studies indicated that kenaf considerably improved the wear and frictional performance of epoxy resins [12], and worked even better on thermoplastic polyesters [13]. More recently, the possibility of further improvement in wear resistance with the addition of carbon nanotubes in kenaf-epoxy composites was also investigated [14]. Additionally, complex hybrids were fabricated, such as kenaf-jute-aloe vera, with some benefit to wear properties [15].…”
Section: Introductionmentioning
confidence: 99%